Heat source estimation in low diffusive materials. Issue 3 (September 2016) - Castillo, A; Gardarein, J-L; Gaspar, J; Rigollet, F; LeNiliot, C
Abstract: In this work, a method to estimate unsteady 2D heat sources is developed. The sources are estimated from Infra-Red (IR) temperature mapping on the front face of thermally thin material. A comparison of the estimation accuracy as well as the evaluation of time cost is also carried out between a direct method (coupled with filtering techniques) and an iterative method (of conjugate gradient type). The present work was realised on experimental data.